The Greek Surgeon-Gynecologist Savvas Georgiadis (1857-1942) and the First Vaginal Reconstruction in Smyrna. (October 2019) - Vladimiros, Lazaros; Tsoucalas, Gregory; Thomaidis, Vasilios; Kakagia, Despoina
The Greek surgeon-gynecologist Savvas Georgiadis from Phocaea in Asia Minor had performed in 1897 an innovative surgical operation in a young female patient, reconstructing her vagina. Having been educated both in Greece and France, specialized in gynecology, he became a famous surgeon in the Hellenic Hospital of Smyrna "Agios Charalampos, " where the operation was masterfully executed. Although among the pioneers in neovagina techniques, Georgiadis still is searching his place among the important figures in the history of plastic surgery.